Uji Aktivitas Antibakteri Fraksi N-Heksan Kulit Bawang Merah (Allium cepa L.) Terhadap Bakteri Streptococcus mutans - Ika Yeni Siahaan; Haris Munandar Nasution; Muhammad Amin Nasution; Yayuk Putri Rahayu (Journal of Pharmaceutical and Sciences, 2023)
Caries, or cavities, is a disease caused by damage to the enamel layer caused by the activity of bacteria in the mouth, one of which is the Streptococcus mutans bacterium. One of the plants that is useful as an antibacterial is the red onion (Allium cepa L.). The objective of this research was to determine the content of secondary metabolites in shallot skin and the antibacterial activity of the n-hexane and ethyl acetate fractions of shallot skin against Streptococcus mutansbacteria. An antibacterial activity test was carried out using the Kirby-Bauer diffusion method using paper discs. Empty Kirby-Baurer disks were dipped for 15 minutes into each solution of the n-hexane fraction and ethyl acetate fraction of shallot skin in various concentrations of 10%, 30%, 50%, and 70%. The positive controls used were amoxicillin disks, and the negative controls used DMSO. The content of secondary metabolites in the ethyl acetate fraction of shallot skins, which are semi-polar, is alkaloids, flavanoids, and tannins. Meanwhile, the n-hexane fraction of shallot skin contains nonpolar compounds, namely saponins and steroids or triterpenoids. The antibacterial test results of the ethyl acetate fraction of shallot skin obtained the diameter of inhibition at a concentration of 10% (7.33 ± 1.52), a concentration of 30% (9.67 ± 1.52), a concentration of 50% (13.33 ± 1, 52), and a 70% concentration (15.67 ± 1.52). While the n-hexane fraction of shallot skin obtained the diameter of the inhibition zone at a concentration of 10% (1.00 ± 1.00), a concentration of 30% (8.67 ± 1.52), a concentration of 50% (9.67 ± 1.52), and a 70% concentration (11.33 ± 1.52). The n-hexane fraction and the ethyl acetate fraction of shallot skin (Allium cepa L.) had antibacterial activity against Streptococcus mutans, with the best inhibition being the ethyl acetate fraction at a concentration of 70% classified as intermediate.